Diagnostic efficacy of positron emission computerized tomography scans in suspicious laryngeal findings postorgan preservation treatment. Issue 1 (27th October 2022) - Warshavsky, Anton; Holan, Ariel; Muhanna, Nidal; Oestraicher, Yael; Nachalon, Yuval; Kampel, Liyona; Nard‐Carmel, Narin; Chaushu, Hen; Shapira, Udi; Ungar, Omer; Gutfeld, Orit; Ospovat, Inna; et al.
Abstract: Background: Larynx preservation protocols (LPP) for glottic primary squamous cell carcinoma has gained popularity worldwide. Direct laryngoscopy (DL) with biopsy is mandated when recurrence is suspected. The efficacy of 18Fluoro‐deoxy‐glucose positron emission computerized tomography (PET‐CT) as alternative first‐line diagnostic investigation in suspected recurrence was evaluated. Methods: A retrospective study of patients with suspicious fiber‐optic findings at more than 12 weeks after LPP. Sensitivity, specificity, and the negative predictive value (NPV) of DL and PET‐CT were compared. Results: Seventy‐two patients presenting 105 cases of suspicious events were included in this study. Fifty‐two events were initially investigated by DL and 53 events by PET‐CT. The sensitivity of DL and PET‐CT was 56.25% and 100%, respectively. The NPV was 84% for DL and 100% for PET‐CT ( p = 0.015). Conclusion: Negative PET scans after LPP are highly accurate in ruling out recurrent/persistent disease and may spare the patient from negative biopsies.